Knee joint dynamics predict patellar tendinitis in elite volleyball players - Richards, D. P.; Ajemian, S. V.; Wiley, J. P.; Zernicke, R. F. (The American Journal of Sports Medicine, 1996)
We quantified the lower extremity dynamics developed during the volleyball spike and block jumps to find out if predictive relations exist between jump dynamics and patellar tendinitis. Lower extremity movement biomechanics were analyzed for 10 members of the 1994 Canadian Men's National Volleyball Team (all right-handed hitters). Based on physical examination, 3 of the 10 players had patellar tendon pain associated with patellar tendinitis at the time of testing. In masked biomechanical and logistic regression analyses, we discovered that the vertical ground-reaction force during the take-off phase of both spike and block jumps was a significant predictor of patellar tendinitis-correctly predicting the presence or absence of patellar tendinitis in 8 of 10 players. Deepest knee flexion angle (during landing from the spike jump) predicted 10 of 10 cases correctly for the left knee. The external tibial torsional moment (during the takeoff for the right knee with the spike jump and for the left knee with the block jump) was also a significant predictor of tendinitis. In these players, the likelihood of patellar tendon pain was significantly related to high forces and rates of loading in the knee extensor mechanism, combined with large external tibial torsional moments and deep knee flexion angles.